The Aesthetics of Mimesis : Ancient Texts and Modern Problems - Halliwell, Stephen (Book collections on Project MUSE., 2002)
Mimesis is one of the oldest, most fundamental concepts in Western aesthetics. This book offers a new, searching treatment of its long history at the center of theories of representational art: above all, in the highly influential writings of Plato and Aristotle, but also in later Greco-Roman philosophy and criticism, and subsequently in many areas of aesthetic controversy from the Renaissance to the twentieth century. Combining classical scholarship, philosophical analysis, and the history of ideas--and ranging across discussion of poetry, painting, and music--Stephen Halliwell shows with a wealth of detail how mimesis, at all stages of its evolution, has been a more complex, variable concept than its conventional translation of "imitation" can now convey.